1979
DOI: 10.1042/bj1820717
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin regulation of the synthesis of a specific rat adrenal cytosolic protein. Effects of hypophysectomy and actinomycin D

Abstract: The mechanism of corticotropin stimulation of the synthesis of a specific rat adrenal cytosolic protein was investigated. This protein (protein E) has a mol.wt. of approx. 30000. It is detected by polyacrylamide-gel electrophoresis of cytosol prepared from adrenal slices from rats treated with corticotropin in vivo and control rats, the slices being incubated with [3H]-and ['4C]-leucine respectively. In rats 1-15 days after hypophysectomy, corticotropin, like dibutyryl cyclic AMP, induces an increase in protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

1980
1980
1986
1986

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
8
2
Order By: Relevance
“…This study confirms and extends previous work from our laboratory [2,3] indicating preferential synthesis of protein E in response to ACTH. In the present study, by using in vitro translation assays, we demonstrate that the increased synthesis of protein E is due to an increased level of its mRNA.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This study confirms and extends previous work from our laboratory [2,3] indicating preferential synthesis of protein E in response to ACTH. In the present study, by using in vitro translation assays, we demonstrate that the increased synthesis of protein E is due to an increased level of its mRNA.…”
Section: Discussionsupporting
confidence: 82%
“…Radioactive amino acid incorporation into adre nal slices from control and ACTH-treated rats was performed as previously described [2,3] except that both ['H]-leucine 200pCi/ml and [,5S]-methionine 200 pCi/ml were used in the incubation. Adrenal cyto solic preparations from control and ACTH-treated rats prepared as detailed elsewhere [2,3] were submit ted to slab polyacrylamide gel electrophoresis.…”
Section: Protein E Purification and Preparation O F Rabbit Antiserummentioning
confidence: 99%
See 1 more Smart Citation
“…In the present experiments in order to increase the duration of the action of Synacthene Retard it was dissolved in saline at pH 10. Under these conditions using the same amount of Synacthene we were able to stimulate total protein synthesis in hypophysectomized rats to about the same extent as in control rats, contrary to what was found when Synacthene Retard was dissolved in saline at pH 7 [10] where no stimulation of total protein synthesis was found in hypophysectomized rats. Most of the experiments were repeated at least three times.…”
Section: Animalscontrasting
confidence: 41%
“…In vitro, corticotropin stimulates the synthesis of a small peptide in a cultured mouse adrenocortical cell line Y( [8], In vivo cortico tropin produces a marked stimulation of the synthesis of a specific adrenal cytosolic protein (protein E) [9], Previous work from this laboratory [10] has shown that the synthesis of this protein is cyclic AMP-dependent and requires mRNA synthesis.…”
Section: Introductionmentioning
confidence: 99%